Office blood pressure threshold of 130/80 mmHg better predicts uncontrolled out‐of‐office blood pressure in apparent treatment‐resistant hypertension. Issue 3 (5th December 2020) - Lee, Chan Joo; Ha, Jeong‐Ha; Kim, Jang Young; Kim, In‐Cheol; Ryu, Sung Kee; Rhee, Moo‐Yong; Lee, Ju‐Hee; Lee, Jung‐Hee; Lee, Hae‐Young; Ihm, Sang‐Hyun; Chung, Joong Wha; Choi, Jung Hyun; et al.
Abstract: The objective of this study was to compare the diagnostic accuracy of office blood pressure (BP) threshold of 140/90 and 130/80 mmHg for correctly identifying uncontrolled out‐of‐office BP in apparent treatment‐resistant hypertension (aTRH). We analyzed 468 subjects from a prospectively enrolled cohort of patients with resistant hypertension in South Korea (clinicaltrials.gov: NCT03540992). Resistant hypertension was defined as office BP ≥ 130/80 mmHg with three different classes of antihypertensive medications including thiazide‐type/like diuretics, or treated hypertension with four or more different classes of antihypertensive medications. We conducted different types of BP measurements including office BP, automated office BP (AOBP), home BP, and ambulatory BP. We defined uncontrolled out‐of‐office BP as daytime BP ≥ 135/85 mmHg and/or home BP ≥ 135/85 mmHg. Among subjects with office BP < 140/90 mmHg and subjects with office BP < 130/80 mmHg, 66% and 55% had uncontrolled out‐of‐office BP, respectively. The prevalence of controlled and masked uncontrolled hypertension was lower, and the prevalence of white‐coat and sustained uncontrolled hypertension was higher, with a threshold of 130/80 mmHg than of 140/90 mmHg, for both office BP and AOBP. The office BP threshold of 130/80 mmHg was better able to diagnose uncontrolled out‐of‐office BP than 140/90 mmHg, and the net reclassification improvement (NRI) was 0.255. The AOBP threshold of 130/80 mmHg also revealed better diagnostic accuracy than 140/90 mmHg, with NRI of 0.543. The office BP threshold of 130/80 mmHg showed better than 140/90 mmHg in terms of the correspondence to out‐of‐office BP in subjects with aTRH.